Comparative effectiveness of adalimumab and etanercept for rheumatoid arthritis in the Brazilian Public Health System. (November 2016) - dos Santos, Jéssica Barreto Ribeiro; Almeida, Alessandra Maciel; Acurcio, Francisco de Assis; de Oliveira Junior, Haliton Alves; Kakehasi, Adriana Maria; Guerra Junior, Augusto Afonso; Bennie, Marion; Godman, Brian; Alvares, Juliana
Aim: Biological disease-modifying antirheumatic drugs (bDMARDs) are used to treat rheumatoid arthritis (RA) with adalimumab and etanercept the most used bDMARDs in Brazil. This open prospective cohort study evaluated their effectiveness and safety among RA patients in the Brazilian Public Health System given their costs.Methods: The Clinical Disease Activity Index was primarily used to assess their effectiveness after 6 and 12 months of follow-up. The Health Assessment Questionnaire and EuroQol-5D were also used.Results : A total of 266 RA patients started treatment with adalimumab or etanercept. Adalimumab was the most widely used bDMARD (70%). In total, 46% achieved remission or low-disease activity at 12 months with no difference in effectiveness between them (p = 0.306). bDMARDs were more effective in patients who had better functionality at treatment onset and had spent longer in education.Conclusion: This real-world study demonstrated that adalimumab and etanercept are equal alternatives for RA treatment and both were well tolerated.